Pain sensitivity and perceptual sensitivity are associated with severity of emotional dysregulation in children with ADHD: a cross-sectional analysis using the Temperament in Middle Childhood Questionnaire. Issue 5 (27th February 2023) - Bruton, Alisha M.; Senders, Angela; Tost, Gabriella; Ast, Hayleigh; Robinette, Lisa M.; Leung, Brenda; Hatsu, Irene E.; Arnold, L. Eugene; Johnstone, Jeanette M.
Abstract: Purpose: Nearly 50% of children with attention-deficit/hyperactivity disorder (ADHD) experience emotional dysregulation or sensory over-responsiveness; this study examines their association. Methods: This cross-sectional analysis ( n = 124) used data from the Micronutrients for ADHD in Youth (MADDY) Study, which enrolled children aged 6–12 with ADHD and emotional dysregulation. Sensory responsiveness was assessed using two subscales from the factor-analyzed Temperament in Middle Childhood Questionnaire: Pain Sensitivity and Perceptual Sensitivity. Emotional dysregulation was assessed using the Emotional-Problems and Conduct-Problems subscales from the Strengths and Difficulties Questionnaire and a composite score from the Child & Adolescent Symptom Inventory-5. Multivariable linear regression measured the association of pain and perceptual sensitivity with the severity of emotional dysregulation. Results: In adjusted models, pain sensitivity was positively associated with Emotional Problems ( β = 0.97; 95% CI: 0.52, 1.41; p < 0.0001), Conduct Problems ( β = 0.83; 95% CI: 0.44, 1.21; p = 0.0001), and CASI-5 composite ( β = 0.25; 95% CI: 0.16, 0.34; p < 0.0001). Perceptual sensitivity was positively associated with Emotional Problems ( β = 0.75; 95% CI: 0.15, 1.35; p = 0.01) but not Conduct Problems ( β = 0.27; 95% CI: −0.24, 0.77; p = 0.30) or CASI-5 composite ( β = 0.12; 95% CI: −0.01, 0.24; p = 0.07). Conclusion: Pain sensitivity was associated with the severity of emotional dysregulation in this ADHD sample. To better understand possible causal links, longitudinal studies are warranted. Implications for rehabilitation: Emotional dysregulation and sensory over-responsiveness are both common in children with ADHD and contribute to added challenges in school and family life. Two types of sensory over-responsiveness, pain sensitivity and perceptual sensitivity, were associated with emotional dysregulation in children with ADHD in our study. Sensory over-responsiveness may be a modifiable treatment target.